Collaboration and Entrepreneurship within Digital Environment - Olga A. Shvetsova (Insights into Economics and Management Vol. 10, 2021)
Companies engage in various international relationships with external stakeholders to create attractive offerings. This book describes the most common online business collaboration concepts in international environment, and compare their characteristics. The concepts are evaluated in terms of their implications for companies, particularly in innovation and big data collaboration contexts. The study is based on the literature findings on common online business collaboration concepts, analyses of their characteristics, and an evaluation of implications from a company’s perspective. The key implications for a company include the need for interaction with various external stakeholders to enhance innovation, opportunities and access to important resources, and the need to prepare for online network changes. While many collaboration concepts are utilized in contemporary business literature, their use in traditional research varies, and the concepts have not been analyzed and compared together within online environment.